Coloniality and indigenous territorial rights in the Peruvian Amazon: A critique of the prior consultation law - Roger Merino Acu\~na (University of Bath, Centre for Development Studies (CDS), 2015)
A massive indigenous protest in the Peruvian Amazon and its aftermaths triggered a social consensus in Peru about the necessity of intercultural policies and the enactment of a Consultation Law, a norm based on the ILO Convention 169 to consult indigenous peoples before approving any norm that can affect indigenous collective rights. Nonetheless, the paper argues that, like previous legal reforms related to the recognition of indigenous rights, the Consultation Law remains conceiving indigenous peoples as minorities with proprietary entitlements instead of conceiving them as nations with territorial rights. The Law is a form of liberal legality still embedded in coloniality. Consequently, indigenous peoples maintain a tense and ambiguous relation with liberal legality: they use the Consultation Law for territorial defence, but at the same time they criticise the limitations of this legislation to fully take into account indigenous cosmologies.
Keywords: 330; Indigenous rights; Consultation Law; self-determination